Bis{benzyl 3-[(1H-indol-3-yl)methylidene]dithiocarbazato-κ(2) N (3),S}palladium(II) N,N-dimethylformamide disolvate - Khaledi, Hamid (International Union of Crystallography, 2010)
In the title compound, [Pd(C(17)H(14)N(3)S(2))(2)]·2C(3)H(7)NO, the deprotonated Schiff base ligand acts as an N,S-bidentate chelate, forming a five-membered ring with the metal atom. The Pd(II) ion, located on an inversion center, is four-coordinated by two of the Schiff base ligands in a square-planar geometry. In the crystal, the indolic NH groups are bonded to the dimethylformamide (DMF) solvent molecules via an N—H⋯O interaction. In addition, C—H⋯S interactions are observed.